1985
DOI: 10.1042/bj2270925
|View full text |Cite
|
Sign up to set email alerts
|

Complexes with halide and other anions of the molybdenum centre of nitrate reductase from Escherichia coli

Abstract: The interconversion of nitrate reductase from Escherichia coli between low-pH and high-pH Mo(V) e.p.r. signal-giving species was re-investigated [cf. Vincent & Bray (1978) Biochem. J. 171, 639-647]. The process cannot be described by a single pK value, since the apparent pK for interconversion is raised by the presence of various anions. The low-pH form of the enzyme exists as a series of complexes with different anion ligands of molybdenum. Each complex has specific and slightly different e.p.r. parameters, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
88
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(101 citation statements)
references
References 19 publications
12
88
1
Order By: Relevance
“…The redox and EPR properties of the active site of membrane Nar obtained from different sources has been the subject of several studies [38,39,40,41,42,43]. Nar enzymes show pH-dependent Mo(V) ion EPR signals having resonances split by a solvent-exchangeable pro- Fig.…”
Section: Membrane-bound Nitrate Reductasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The redox and EPR properties of the active site of membrane Nar obtained from different sources has been the subject of several studies [38,39,40,41,42,43]. Nar enzymes show pH-dependent Mo(V) ion EPR signals having resonances split by a solvent-exchangeable pro- Fig.…”
Section: Membrane-bound Nitrate Reductasesmentioning
confidence: 99%
“…The Mo-bis-MGD, FeS clusters, and heme groups are represented as color-coded balls-and-sticks. .001, g 2 =1.986, g 3 =1.966, A av =9.3 G) and high pH (g 1 =1.987, g 2 =1.981, g 3 =1.962, A av =3.4 G) [39]. The catalytic role of these species is still in debate.…”
Section: Membrane-bound Nitrate Reductasesmentioning
confidence: 99%
“…The redox and electron paramagnetic resonance (EPR) properties of the active site of membrane-bound nitrate reductases obtained from different sources have been the subject of several studies [9,[18][19][20]. Nars show pH-dependent Mo(V) ion EPR signals with resonances split by a solvent-exchangeable proton.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structures of NarGHI and NarGH from Escherichia coli, solved at a resolution of 1.9 Å [16] and 2.0 Å [17], respectively, showed that the catalytic NarG subunit (118-150 kDa) contains the molybdenum site and one [4Fe-4S] cluster (FS0), the NarH subunit (55-64 kDa) contains one [3Fe-4S] cluster (FS4) and three [4Fe-4S] clusters (FS1, FS2, and FS3), and the NarI subunit (19)(20)(21)(22)(23)(24)(25)(26) contains two b-type hemes (b P and b D ). All the redox cofactors are located along an electron transfer pathway (b D -b P -FS 4 -FS 3 -FS 2 -FS 1 -FS 0 -Mo) from which the nitrate receives the electrons provided by the quinol pool [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation